Parental Monitoring and Alcohol Use among Mexican Students - Strunin, Lee (2013)
Parental monitoring has been described as a protective factor and useful strategy to prevent substance misuse among youths. The aims of this study were to examine whether perceived parental monitoring influences frequency of alcohol use, age of drinking onset and risky drinking among entering public high school and university students in Mexico City. The study is a cross-sectional survey of entering first year students in the high school and university school system of a large public university in Mexico City conducted during registration at the beginning of the school year. In 2008, of 34,840 students accepted to the affiliated high schools, 28,996 students (51.8% female) completed the alcohol survey and of 37,683 students accepted into university 30,084 students (51.5% female) completed the alcohol survey. The findings suggest that compared to students with higher perceived parental monitoring those reporting lower perceived parental monitoring were more likely to report risky behavior. They were more likely to be ever drinkers, frequent drinkers, have earlier age of onset and high AUDIT scores. Overall, higher parental monitoring was strongly associated with being female and lower parental monitoring with being male. Our findings suggest that more research on parental monitoring as a protective strategy against alcohol misuse is needed. Research focusing on cultural factors including gender and age-related norms and familismo would increase knowledge of the association of parental monitoring and alcohol use among Mexican youths, Mexican American youths and potentially youths from other Hispanic backgrounds.